Challenges and Strategies in Addressing Fake News in the Digital Age - Nugraha, Budi; Purwitasari, Ira (COMMENTATE: Journal of Communication Management, 2025)
Fake news is a major challenge in modern journalism in this digital era. Although mainstream media have strict journalistic standards, they can inadvertently popularize fake news. Mainstream media can also increase public exposure to fake news through moral efforts to correct incorrect reporting. This article highlights fake news mitigation practices in Indonesian mainstream media through a literature review approach of previous research and direct observation of eight online news media: detiknews, kompas.com, liputan6.com, okezone, republika, sindonews, tempo.co, and tribunnews.com. The results of the study show that online media are aware of the importance of maintaining credibility amidst the rapid flow of digital information, the balance between meeting readers' information needs instantly and maintaining news credibility, media awareness of the importance of digital literacy among the public, and the importance of maintaining morality amidst online media competition. Several suggestions are given so that mainstream media are better able to improve their quality by reporting high-quality news and preventing fake news from spreading in the community.